Contributions to Celtiberian Etymology III: The Bronze of Novallas (Z.02.01) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
This article makes etymological proposals for five words in the Celtiberian inscription from Novallas (Z.02.01): the place name TERGAⱾ is connected with Western Indo-European *tergo- ‘market’; DOIBIM is explained as a dative dual *dou̯ibim ‘to the two’; the gerund DVNDOM ‘to give’ is analysed as *dh₃(u)-un-do-; MEDOM is compared with Old Irish med ‘measure, balance’ and Welsh medd ‘authority’; and the fragmentary DERNV[ is compared with words for ‘hand’ or ‘palm’ in other Celtic languages. It is suggested to transcribe the new sibilant sign of Celtiberian with Ȿ (Unicode 2C7E).
Keywords: Bronze of Novallas; Celtiberian; etymology; sibilant transcription